2017
DOI: 10.1097/dcr.0000000000000822
|View full text |Cite
|
Sign up to set email alerts
|

Management of Low Colorectal Anastomotic Leakage in the Laparoscopic Era: More Than a Decade of Experience

Abstract: Laparoscopic anterior resection is associated with low levels of complications, including anastomotic leak, postoperative mortality, and permanent stoma formation. Anastomotic leakage can be managed with laparoscopy in the majority of cases. See Video Abstract at http://links.lww.com/DCR/A353.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
61
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 34 publications
4
61
0
7
Order By: Relevance
“…The management of AL is challenging [8][9][10][11]. Traditionally, surgical resection of the anastomosis with proximal stoma formation has been the treatment of choice.…”
Section: Introductionmentioning
confidence: 99%
“…The management of AL is challenging [8][9][10][11]. Traditionally, surgical resection of the anastomosis with proximal stoma formation has been the treatment of choice.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 1.5% of surgical procedures performed in Wisconsin are complicated by SSIs, and the Centers for Disease Control and Prevention (CDC) reports that mortality associated with SSIs has been reported to be as high as 3% nationally . Specific case scenarios (ie, organ or body space infections after laparoscopic colorectal surgeries in which anastomotic leaks occurred) have been associated with a 30‐day mortality rate of 4.5% . Furthermore, the fiscal burden of these adverse events approaches $10 billion annually in the United States .…”
mentioning
confidence: 99%
“…Permanent stoma occurred in 1.8% of our patients, or one‐third of patients with AC, whether AL or AS. The incidence of permanent stoma after transient diversion is reported to range from 3% to 60% . Restoration failure in patients with AL was due mostly to recurrences and intractable pelvic inflammation, whereas restoration failure in patients with AS was due mostly to recurrences and obstinate stenosis …”
Section: Discussionmentioning
confidence: 99%
“…The incidence of permanent stoma after transient diversion is reported to range from 3% to 60%. 26,27 Restoration failure in patients with AL was due mostly to recurrences and intractable pelvic inflammation, whereas restoration failure in patients with AS was due mostly to recurrences and obstinate stenosis. 27 We found that AL as an independent risk factor for DFS, as reported in many previous studies and meta-analyses, 3,28,29 although a recent study did not find any correlation between AL and poor survival outcome in patients who received preoperative CRT.…”
Section: Discussionmentioning
confidence: 99%